A Bézier Degree Elevation Trajectory Optimization Algorithm for Flying Chip-Ejection Mass Transfer Technology - Sun, Jianfeng; Chen, Xun; Lin, Guohuai; Yao, Jingsong; Chen, Xin (IEEE/ASME transactions on mechatronics, 2025)
In this article, a trajectory optimization algorithm is proposed for flying chip ejection mass transfer technology, using the Bézier degree elevation techniques. First, by converting the flying chip ejection requirements into equations and inequalities, the optimization problem of flying chip ejection is constructed. Then, the Bézier curve and the degree elevation are introduced, which expand the search space for the original problem as proven by a theorem on point and curve constraints. After that, a Bézier degree elevation optimization algorithm is proposed. Comparisons with previous algorithms in simulations and platform experiments verify the effectiveness of the proposed algorithm. Results show that the proposed algorithm is more suitable for optimization problems with strict constraints.